Pemanfaatan Instrumen IWA 2 untuk MenentukanArea For Improvement dalam Rangka Peningkatan Mutu Berkelanjutan (Studi Kasus Fakultas Teknik Unika Atma Jaya) - MM. Wahyuni Inderawati; Christine Natalia; Feliks Prasepta S.Surbakti (Jurnal METRIS, 2013)
The philosophy of quality management system ISO 9001:2008 is continuous improvement. To achieve thequalilty objective, an organization must develop a systematic and consistent continuous improvementprogram. The Faculty of Engineering, Atma Jaya Catholic University (FT UAJ) has adopted the ISO9001:2008 quality management system since 2010, however, they still have discrepancy in theimplementation. IWA 2 guide can be a reference for developing a continuous improvement of this system. Theresults of this study showed that the FT UAJ still need to do some aspects of continuous improvement that isa weakness in providing motivation to students, the lack of monitoring of process improvement competency,integrated data management including data derived from outside the institution, customer satisfactionmeasurement, actions to meet the needs of community members ( faculty, staff education, student), and aclear organizational goal. The results confirmed the findings of the internal audit report, there isconcordance between the results of the survey with the findings of the internal audit report. This study is apart of multi –year research, and this paper is the result of the first year of research that aims to providerecommendations on Areas for Improvement / AFI in FT UAJ .